Effect of N-acetylcysteine plus deferoxamine on oxidative stress and inflammation in dystrophic muscle cells. (May 2015) - Moraes, Luis Henrique Rapucci; Bollineli, Roberta Constâncio; Mizobuti, Daniela Sayuri; Silveira, Leonardo dos Reis; Marques, Maria Julia; Minatel, Elaine
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Oxidative stress and inflammatory process play an important role in the pathogenesis of Duchenne muscular dystrophy (DMD). We investigated whether deferoxamine (DFX) improves the antioxidant effects of N-acetylcysteine (NAC) on primary cultures of dystrophic muscle cells from mdx mice, the experimental model of DMD. Methods Primary cultures of skeletal muscle cells from mdx mice were treated with either NAC (10 mM), DFX (5 mM), or NAC plus DFX for 24 hours. The muscle cells of C57BL/10 mice were used as controls. Results Production of hydrogen peroxide (H2O2) and levels of 4-hydroxynonenal (4-HNE), tumor necrosis factor alpha (TNF-α), and nuclear factor kappa-B (NF-κB) were significantly higher in mdx muscle cells than in C57BL/10 muscle cells. Treatment with NAC, DFX, or NAC plus DFX significantly decreased H2O2 production (24, 58, and 72%, respectively), and levels of 4-HNE-protein adducts (62, 33, and 71%, respectively), TNF-α (32, 29, and 31%, respectively), and NF-κB (34, 38, and 52%, respectively) on dystrophic muscle cells. Discussion This study demonstrates that mdx muscle cells are able to produce key oxidative stress and inflammatory markers, without the interference of inflammatory cells, and shows that NAC plus DFX reduced the inflammatory and oxidative stress indicators, mainly H2O2 production and NF-κB levels by dystrophic fibers.